Urethane-induced hyperglycemia - Wang Min-Yan; Ren Lei-Ming; Du Zhan-Jiang; Fu Shao-Xuan (Acta Pharmacologica Sinica, 2016)
"AIM: To study the effects of urethane, at anesthetic dose, on the blood glucose levels in normal rats and hyperglycemic rats, and its effects on the hypoglycemic action of exogenous insulin in alloxan-treated rats. METHODS: Blood glucose concentration was measured with the glucose oxidase method. RESULTS: Urethane at anesthetic dose 1.5 g.kg-1 increased the blood glucose levels in fasting (to 2.6 +/- 0.3 g.L-1, P < 0.01) or glucose-loaded (to 3.9 +/- 0.4 g.L-1, P < 0.01) rats. It did not modify the hyperglycemia induced by epinephrine (normal islet beta-cells) or alloxan (impaired islet beta-cells). In the rats treated with alloxan, blood glucose level decreased to 1.8 +/- 0.7 g.L-1 at 200 min after administration of insulin from control level of 7.0 +/- 2.3 g.L-1, but the hypoglycemic action of exogenous insulin was abolished by urethane. CONCLUSION: Hyperglycemic action of urethane was due to its inhibiting effect on the hypoglycemic effect of insulin, except for its known mechanism of increased sympathetic release."